Tumor budding in cervical carcinoma: associations with some clinical and pathological factors - Stanulović, Nevena; Ivković-Kapicl, Tatjana; Mandić, Aljoša; Gutić, Bojana (Archive of Oncology, 2020)
Background: Tumor budding is recognized as an important independent prognostic factor in colorectal carcinoma. The aim of this study was to evaluate the grade of tumor budding and association with other clinical and pathological features in patients with cervical carcinoma. Material and methods: We evaluated pathohistological data from 91 cervical carcinoma patients (mean age: 53.8 years) who underwent radical hysterectomy and pelvic lymphatic dissection at the Oncology Institute of Vojvodina between January 2010 and December 2018. Tumor budding was evaluated in invasive front of the tumor. Based on the number of bud counts/10 high power field, three groups were formed: with no budding, with less than 15 buds, and with more than 15 buds. Results: Eighty (87.91%) of evaluated cervical carcinomas were squamous-cell type, while 12.09% were adenocarcinomas. All carcinomas were graded (HG1-HG3). Average diameter of the tumors was 25 mm (81.6% < 4 cm and 18.4% > 4 cm). Metastases in lymph nodes were present in 30 (32.9%) cases. Based on the number of bud counts/10 high power field there were 35.1% with no budding, 32.9% with less than 15 buds and 37.3% with more than 15 buds. There was a significant association between tumor budding grade and histological grade (p=0.04), as well as with tumor budding grade and the diameter of the tumor (p=0.04). Conclusion: As a quantitative measure of cancer cell dissociation, tumor budding is associated with poor prognosis in cervical carcinoma and should be considered as a prognostic factor.